First catalyst-free CO2 trapping of N-acyliminium ions under ambient conditions: sustainable multicomponent synthesis of thia- and oxazolidinyl carbamates. Issue 37 (17th September 2018) - Franz, Max; Stalling, Timo; Steinert, Henning; Martens, Jürgen
Abstract : A sustainable multicomponent approach through catalyst-free utilization of carbon dioxide under ambient conditions for the preparation of carbamates is reported. Abstract : The first trapping of N -acyliminium ions by in situ generated carbaminic acid (product of carbon dioxide (CO2 ) and amine) is reported. This catalyst-free reaction provides a convenient and feasible approach to prepare N -acyl thia- and oxazolidinyl carbamates with good functional-group compatibility and high efficiency under green conditions. Furthermore, the multicomponent method features a broad substrate scope, facile product diversification, smooth scale-up and notable potential for polymer applications.